2021
DOI: 10.3390/en14123638
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development, Financial Inclusion and Primary Energy Use: Evidence from the European Union Transition Economies

Abstract: The main objective of the research is to analyze the impact of financial sector development indicators and financial institutions access on primary energy use based on a sample of European Union transition members over 20 years period (1996–2017) through panel cointegration and causality tests that allow for cross-section dependence. The causality analysis revealed that the direction of the causality among financial development indicators, financial institutions access, and primary energy use varied among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Table 5 (column 3) shows that financial development as represented by domestic credit (LDC) mitigates shadow economy in OIC countries and non-OIC countries. This is in line with previous studies (Bayar and Ozturk, 2016;Berdiev and Saunoris, 2016), who found that an increase in financial development significantly reduces shadow economy. Market participants would move to shadow economy if they face obstacles to raise funds in the capital market (Kaufmann and Kaliberda, 1996).…”
Section: Financial Development and Shadow Economysupporting
confidence: 93%
“…Table 5 (column 3) shows that financial development as represented by domestic credit (LDC) mitigates shadow economy in OIC countries and non-OIC countries. This is in line with previous studies (Bayar and Ozturk, 2016;Berdiev and Saunoris, 2016), who found that an increase in financial development significantly reduces shadow economy. Market participants would move to shadow economy if they face obstacles to raise funds in the capital market (Kaufmann and Kaliberda, 1996).…”
Section: Financial Development and Shadow Economysupporting
confidence: 93%
“…Furthermore, they have argued regarding absence of policy synergies between growing financial inclusion and mitigating emissions. Bayar et al ( 2021 ) have asserted that financial development has the positive influence on energy usage by augmenting economic growth. Access to financial institutions can also have a beneficial effect on energy consumption by facilitating access to credit for individuals and businesses, which will promote investments and upsurge demand for energy-oriented goods (Ma and Fu 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Access to financial institutions can also have a beneficial effect on energy consumption by facilitating access to credit for individuals and businesses, which will promote investments and upsurge demand for energy-oriented goods (Ma and Fu 2020 ). Nonetheless, financial inclusion makes economic units to have more energy efficient investments and commodities (Bayar et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies examine financial inclusion along several dimensions of development. For instance, Bayar et al (2021) analyze how the usage of primary energy is affected by financial sector development and access to finance. They analyze a sample of European Union (EU) transition countries from 1996 to 2017 using panel co-integration and causality tests that allow for cross-section dependence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies examine financial inclusion along several dimensions of development. For instance, Bayar et al. (2021) analyze how the usage of primary energy is affected by financial sector development and access to finance.…”
Section: Literature Reviewmentioning
confidence: 99%